Bacteria and macrophages in the tumor microenvironment - Xu, Shiyao; Xiong, Yan; Fu, Beibei; Guo, Dong; Sha, Zhou; Lin, Xiaoyuan; Wu, Haibo (Frontiers in Microbiology, 2023)
Cancer and microbial infections are significant worldwide health challenges. Numerous studies have demonstrated that bacteria may contribute to the emergence of cancer. In this review, we assemble bacterial species discovered in various cancers to describe their variety and specificity. The relationship between bacteria and macrophages in cancer is also highlighted, and we look for ample proof to establish a biological basis for bacterial-induced macrophage polarization. Finally, we quickly go over the potential roles of metabolites, cytokines, and microRNAs in the regulation of the tumor microenvironment by bacterially activated macrophages. The complexity of bacteria and macrophages in cancer will be revealed as we gain a better understanding of their pathogenic mechanisms, which will lead to new therapeutic approaches for both inflammatory illnesses and cancer.